Pengaruh Media Video terhadap Kemampuan Siswa Kelas IX Farmasi SMK Baznaz Sulawesi Selatan Mengapresiasi Drama Bukan Alosi Ripolo Dua Karya Aruel Sederhana - Ririn Sabriadi (Journal on Education, 2023)
This study aims to describe the effect of video media on students' ability to appreciate the drama "Not Alosi Ripolo Dua" by Aruel Modest in class XI Pharmacy at SMK Baznas South Sulawesi. This type of research is pre-experimental research, namely an experiment which in its implementation only involves one class as an experimental class without any comparison class (control class). The experimental unit in this study were 16 students of class XI Pharmacy. The research was conducted for 4 meetings. The success of the learning process in terms of aspects, namely; creating new video-based learning resources and increasing aspects of student knowledge related to appreciating drama. The data collection technique used is data on the acquisition score of learning outcomes before using the video and after using the video media collected using the Pretest-Postest test. The results of the descriptive statistical analysis that has been carried out concluded that there was an effect of the use of video media on the knowledge of appreciating drama in class XI Pharmacy class XI Pharmacy SMK Baznas South Sulawesi based on the results of the average value (mean) showing that student learning outcomes before being given treatment were 73.12. while the average value of student learning outcomes after being given treatment was 82.50. In addition, from the results of the t-test it is known that the value of tcount ≥ ttable or 2.533 ≥ 2.131. So it can be concluded that H0 is rejected by Ha. This means that there is a significant influence of the video media model in appreciating the drama No Alosi Ripolo Dua by Aruel Modest, a class XI Pharmacy student at Baznas Vocational School, Sulawesi Selaan